Reformative Theory of punishment and Principles and Practices for Probation Laws : A Review - Bansal, Bindu (Innovative Research Thoughts, 2018)
Reformative Theory of punishment has achieved worldwide support in recent years and all civilized nations and more particularly socialistic and the democratic countries of the world have adopted various measures and statutory enactments, to apply correctional method of punishment. Reform the criminal and not punish him, is the consensus of the opinion of the modern Criminologists all over the world these days. The modern criminal jurisprudence has emphasized that no one is a born criminal. Man turns into a criminal by force of the circumstances like abject poverty and the other circumstantial and environmental conditions, and not by choice. Thus, Reformative Theory of Punishment is more applicable to a civilized society. Release the offender on probation is one kind of Reformative process – whereby the needs of the community are balanced with the best interests of the offender.